The role of the Evangelical Lutheran Church in Namibia (ELCIN) as a pioneer of social development through education in Ovamboland (1870-1970) : a church historical study - Nangula, Eino M. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.